A Comprehensive Review on Chemical Profile and Pharmacological Activities of Ocimum basilicum. Issue 1 (2nd January 2023) - Dhama, Kuldeep; Sharun, Khan; Gugjoo, Mudasir B.; Tiwari, Ruchi; Alagawany, Mahmoud; Iqbal Yatoo, Mohd.; Thakur, Pallavi; Iqbal, Hafiz M.N.; Chaicumpa, Wanpen; Michalak, Izabela; Elnesr, Shaaban S.; Farag, Mayada R.
ABSTRACT: Herbs and plant metabolites/extracts are gaining wide attention owing to their multiple beneficial health effects, medicinal values, and nutraceutical properties, particularly in the present era of emerging drug resistance and untold side effects of chemical drugs. Ocimum basilicum L., known as sweet basil, has been studied for its various potent effects including, antimicrobial, antifungal, insecticidal, antiparasitic, antioxidant, immunomodulatory, anti-inflammatory, hepatoprotective, anti-osteoporotic, cardioprotective, neuroprotective, anti-cancer, and other beneficial health effects. Thus, this herb has the potential for treating a myriad of ailments/diseases and disorders in both humans and animals. Different bioactive chemical compounds have been identified from O. basilicum, such as linalool, geraniol, methyl eugenol, methyl chavicol, p -allylanisole, 1, 8–cineole, trans–α–bergamotene, and neryl acetate. Recent advances in nanotechnology can further be utilized for improving the multiple beneficial activities of the crude extract of O. basilicum . This review highlights the phytoconstituent profile, medicinal values, therapeutic applications, and salient beneficial health aspects of O. basilicum, which would help in further exploring this wonderful herb for designing effective pharmaceuticals, drugs and medicines for safeguarding various health issues of humans and animals, while supporting its traditional use in curing various ailments, diseases and health-promoting effects.